Therapeutic bioactive of pandanus Amaryllifolius Roxb leaves for functional food application: article / Putri Ani Narisa Ahmad Bakhtiar - Ahmad Bakhtiar, Putri Ani Narisa (2018)
Over the years, many researchers and the people in food industry have become increasingly interested in phenolic compounds in natural food source, mainly due to the current growing interest for natural antioxidants. The conventional or traditional way of extraction have a few downside in terms of extraction time and the extraction yield. Microwave assisted extraction (MAE) is one of the advance technology developed for the purpose of extraction. The purpose of this research is to study the effect of microwave power level on extraction of Pandanus Amaryllifolius Roxb leaves and to compare the total phenolic content (TPC) and antioxidant activity of traditional and microwave-extracted Pandanus Amaryllifolius Roxb leaves. The parameters that we varies during this experiment is the solvent concentration, soaking temperature and power level of the microwave. Both of the method were subjected to average 10 minutes of extraction. From the results of the experiment, MAE produce higher yield of TPC compared than that of soaking method with value 1.557 mg/g GAE and 0.979 mg/g GAE respectively. The result also established a linear correlation between total phenolic content (TPC) and antioxidant scavenging activity with R2 value is 0.915.